1988
DOI: 10.1038/bjc.1988.89
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity and haemoglobin synthesis induction by cytidine analogues

Abstract: Summary We investigated 5-azacytidine and five of its analogues for: (1) carcinogenicity, in the male Fischer rat; (2) toxicities using changes in rat weights in vivo and a cytotoxicity assay in vitro; and (3) haemoglobin gene expression, using minor haemoglobin synthesis in sheep, mice and rats. 5-Azacytidine was found to be a complete carcinogen. It increased the incidence of testicular tumours as well as non-testicular tumours in rats treated for 12 months. 5-Azacytidine also had hepatic tumour promoting pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

1990
1990
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 49 publications
(55 reference statements)
0
19
0
4
Order By: Relevance
“…Multicycle repeated-dose toxicity studies in rats and rabbits indicated that the primary toxicity was myelosuppression, which was reversible on cessation of treatment [28][29][30][31][32]. Gastrointestinal toxicity was also observed.…”
Section: Nonclinical Aspects and Clinical Pharmacologymentioning
confidence: 99%
“…Multicycle repeated-dose toxicity studies in rats and rabbits indicated that the primary toxicity was myelosuppression, which was reversible on cessation of treatment [28][29][30][31][32]. Gastrointestinal toxicity was also observed.…”
Section: Nonclinical Aspects and Clinical Pharmacologymentioning
confidence: 99%
“…22 An early study reported that this agent was not carcinogenic in the rat model. 7 More interestingly, recent studies have shown that treatment of mice with a genetic disposition for colon or lung cancer with decitabine results in a marked reduction in tumor formation. 23,24 It is believed that this reduction in tumorogenesis may reflect demethylation of tumor suppressor genes.…”
Section: Decitabinementioning
confidence: 99%
“…In spite of these promising preliminary results, this agent was never tested in large-scale clinical trials due to concerns about its potential carcinogenic effects, since a previous study conducted in laboratory rats showed that 5-azacytidine increased the incidence of tumors. 7 Interestingly, controversy over the mechanism of induction of HbF by 5-azacytidine led to the studies which showed that hydroxyurea, another cytostatic agent, can also result in a marked induction of HbF in Baboons. 8 …”
Section: -Azacytidinementioning
confidence: 99%
“…For instance, given the effect of global DNA hypomethylation on genomic stability, therapyinduced hypomethylation might promote tumor formation on the long run, although this hypothesis still needs verification (Eden et al, 2003;Yang et al, 2003). Epigenetic therapy might also cause activation of imprinted or silenced genes and has indeed been shown to be mutagenic and possibly even carcinogenic (Carr et al, 1988;Jackson-Grusby et al, 1997). However, these concerns should not be exaggerated, as DNMT inhibitors only act on dividing cells, while leaving other cells unaffected.…”
Section: Epigenetic Cancer Therapymentioning
confidence: 99%